2004
DOI: 10.1111/j.1600-079x.2004.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of melatonin and its catabolites, N1‐acetyl‐N2‐formyl‐5‐methoxykynuramine and N1‐acetyl‐5‐methoxykynuramine, by activated leukocytes

Abstract: N(1)-acetyl-N(2)-formyl-5-methoxykynuramine (AFMK) and N(1)-acetyl-5-methoxykynuramine (AMK), two melatonin catabolites, have been described as potent antioxidants. We aimed to follow the kinetics of AFMK and AMK formation when melatonin is oxidized by phorbol myristate acetate (PMA) and lipopolysaccharide (LPS)-activated leukocytes. An HPLC-based method was used for AFMK and AMK determination in neutrophil and peripheral blood mononuclear cell cultures supernatants. Samples were separated isocratically on a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 18 publications
3
87
0
4
Order By: Relevance
“…It remains to be studied whether microglia responds in a similar way to melatonin and AFMK. Activated microglia could convert melatonin by two enzymes, indoleamine 2,3-dioxygenase, although its main substrate is tryptophan, not melatonin [50,51,122,132], and myeloperoxidase [27,50,111,123,157,158]. Additionally, melatonin might be oxidized to AFMK by reactive oxygen species [38,39,47,50,136,141] transiently formed in excess.…”
Section: The Kynuramine Pathwaymentioning
confidence: 99%
“…It remains to be studied whether microglia responds in a similar way to melatonin and AFMK. Activated microglia could convert melatonin by two enzymes, indoleamine 2,3-dioxygenase, although its main substrate is tryptophan, not melatonin [50,51,122,132], and myeloperoxidase [27,50,111,123,157,158]. Additionally, melatonin might be oxidized to AFMK by reactive oxygen species [38,39,47,50,136,141] transiently formed in excess.…”
Section: The Kynuramine Pathwaymentioning
confidence: 99%
“…Some melatonin metabolites that have scavenger properties, like N 1 -acetyl-N 2 -formyl-5-methoxykynuramine (AFMK) and N 1 -acetyl-5-methoxykynuramine (AMK), [55] help inactivate immune-competent cells [8,56] .…”
Section: Shuttle Between Endocrine and Paracrine Melatonin Sources Atmentioning
confidence: 99%
“…We have found that neutrophils and macrophages oxidize melatonin to a chemiluminescent product, presumably N 1 -acetyl-N 2 -formyl-5-methoxykynuramide (AFMK) (21)(22)(23). The reaction required superoxide and was blocked by azide, which is an inhibitor of heme enzymes.…”
mentioning
confidence: 99%